PTH-006 Experience in the use of self-expandable metal stents for the management of variceal haemorrhage. (22nd June 2015) - Ososanya, A; Pick, H; Kayani, J; Austin, A; Salmon, C; Taylor, N; Lawson, A
Abstract : Introduction: Self-Expandable Metal Stents (SEMS) have been reported in small case series to be effective in controlling bleeding from oesophageal varices. A NICE technology appraisal published in 2008 (updated 2011) approved their use, providing arrangements were in place to audit practice. We describe our experience of SEMS in patients presenting with variceal haemorrhage. Method: The Royal Derby Hospital has 24/7 provision of emergency endoscopy by a consultant gastroenterologist and TIPSS insertion available within normal working hours. A SEMS (SX-ELLA Danis) was inserted in 15 patients (M:F 12:3, mean age 56, range 29–73) presenting with variceal haemorhage between 2009 and 2014. All stents were inserted under endoscopic guidance. Portal hypertension was due to alcohol induced cirrhosis (n = 14) and Budd Chiari (n = 1). The median Child Pugh score was 11 (B=2/ C =13) and MELD 21 (range 12–35). All patients had band ligation therapy prior to SEMS insertion, with 6 patients having two attempts at endoscopic treatment and 8 patients having a Sengstaken-Blakemore Tube (SBT). The indication for SEMS insertion was ongoing variceal haemorrhage (n = 4), bleeding from band ligation ulceration (n = 7), a combination of the above (n = 2) or complication of SBT insertion (n = 2). SEMS was used as a bridge to TIPSS in 3 patients (though unsuccessful in 2), but TIPSS was felt to be contraindicated in 11 patients due to the severity of hepatic decompensation and in 1 patient due to portal vein thrombosis. Results: SEMS insertion was successful and immediate haemostasis achieved in all 15 patients. One patient developed aspiration pneumonia, but patients were subsequently nursed at 45° and received a prokinetic, without further incidence of aspiration. Stent migration into the stomach was observed in 3 patients, with partial slip across the gastro-oesophageal junction seen in a further 2 patients. The SEMS were removed from 9 patients after a median of 11 days (range 1–18) without complication. The remaining 6 patients died prior to removal. No patients had evidence of ongoing bleeding while SEMS in situ, but 33% had rebleeding within 30 days of removal. A median of 7 units of blood were transfused pre-SEMS insertion and 2 units post. Patient survival was 40% at 30 days and 27% at 1 year. Amongst survivors at 1 year the median Child Pugh/ MELD score at SEMS insertion was 8.5/ 14 compared to 11/ 24 in those who died. Conclusion: Our experience shows that SEMS can be safely inserted and effectively achieve haemostasis in patients with refractory haemorrhage from oesophageal varices and in those with bleeding from band ligation induced ulceration. Patient survival was poor, however, due to the severity of hepatic decompensation in the study population. Disclosure of interest: None Declared.